MRCP 1 : Clinical Pharmacology, Immunology, Rheumatology, Infectious Diseases (Knutsford PASTEST, 2005)
Part of "MRCP 1 Pocket Book" series, this book features questions and answers providing essential practice for the MRCP Part 1 exam.